Photoprotective effect of the fucose-containing polysaccharide FucoPol. (1st May 2021) - Guerreiro, Bruno M.; Freitas, Filomena; Lima, João C.; Silva, Jorge C.; Reis, Maria A.M.
Graphical abstract: Highlights: The fucose-containing polysaccharide FucoPol shows high UV–vis absorption yield. FucoPol is highly photostable following cumulative irradiation periods. FucoPol concentrations 0.2 % and above optimize UVA/B dual protection. Normalized sun protection factor (SPF) is 60-fold higher than common organic filters. FucoPol showed photoprotective potential to irradiated epithelial cells. Abstract: This study reports the performance of FucoPol, a fucose-containing bacterial polysaccharide, as a photostable agent with high absorption yield at concentrations as low as 0.02 % (w/v). FucoPol is non-cytotoxic, efficiently protects from UVA and UVB at concentrations of 0.02–2 % (w/v) and 0.2–2 % (w/v), respectively, has over 94 % overall photostability up to 1.5 h of irradiation time. The lowest concentration studied (0.02 %, w/v) shows a sun protection factor (SPF) of 2.61 ± 0.08. The SPF-to-concentration unit ratio showed that FucoPol is about 60-fold more photoprotective than combinations of common organic and inorganic UV filters. In vitro radiation exposure experiments of adhered Vero epithelial and PM1 keratinocytic cells in the presence of 0.25 % (w/v) FucoPol further showed that cell viability was preserved, and delayed radiation-induced cell death was prevented. Overall, FucoPol outperforms common cosmetic biopolymers like xanthan and fucogel. These results are very promising for the development of bio-based sunscreen formulations.